2018
DOI: 10.1002/jcb.26588
|View full text |Cite
|
Sign up to set email alerts
|

Lnc RNA SNHG20 participated in proliferation, invasion, and migration of breast cancer cells via miR‐495

Abstract: To explore the mechanism of lnc SNHG20 in the regulation of proliferation, invasion, and migration of breast cancer cells. mRNA levels of SNHG20, miR-495, and HER2 were detected by qRT-PCR. Protein level of HER2 was measured by Western blot. Cell proliferation, invasion, and migration were detected by CCK-8 assay, Boyden chamber assay, and Transwell assay. The combination between SNHG20 and miR-495 was confirmed by RNA pull down assay. The combination between miR-495 and HER2 was confirmed by luciferase report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 23 publications
(38 reference statements)
0
63
0
Order By: Relevance
“…Besides, high‐expression of SNHG20 was observed in human gastric cancer cell lines . Similar results about the high‐expression status of SNHG20 expression were found in female common cancers including cervical cancer , ovarian cancer and breast cancer . The expression of SNHG20 in osteosarcoma was still unknown.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Besides, high‐expression of SNHG20 was observed in human gastric cancer cell lines . Similar results about the high‐expression status of SNHG20 expression were found in female common cancers including cervical cancer , ovarian cancer and breast cancer . The expression of SNHG20 in osteosarcoma was still unknown.…”
Section: Discussionmentioning
confidence: 59%
“…Besides, Li et al revealed silencing of SNHG20 inhibited cell proliferation, invasion, and migration, and cell cycle progression in colorectal cancer . The oncogenic function of SNHG20 was also observed in gastric cancer , cervical cancer , ovarian cancer , and breast cancer .…”
Section: Discussionmentioning
confidence: 99%
“…SNHG20 down-regulates p21 and E-cadherin in ovarian cancer (177), activates STAT6 in hepatocellular carcinoma (178), represses miR140 in laryngeal squamous cell carcinoma (179), modulates ATM (ataxia telangiectasia mutated)-JAK (janus kinase 2)-PD-L1 (programmed death-ligand 1) pathway in esophageal carcinoma (180), up-regulates TGF-B1 in nasopharyngeal carcinoma (181), and enhances EMT and apoptosis via miR-139 -RUNX2 (runt-related transcription factor 2) in osteosarcoma (182,183). In breast cancer, SNHG20 causes miR-495 sponging (184), while in oral cancer, it induces cell proliferation via down-regulating PCNA and Ki67 (185) and via targeting miR-197/LIN28 axis (186). SNHG20, like all SNHG transcripts, is involved in many biological processes, such as: cell proliferation, cell cycle progression, tumorigenesis, apoptosis evasion, and resistance to therapy.…”
Section: Small Nucleolar Rna Host Gene 20 (Snhg20)mentioning
confidence: 99%
“…The small nucleolar RNA host gene 20 (SNHG20) lncRNA is located on 17q25.2 and contains 2,183 nucleotides. Several studies have reported that SNHG20 is involved in promoting several common types of human cancer, including hepatocellular carcinoma (Hcc) (14,15), non-small cell lung cancer (NScLc) (16), colorectal cancer (17), ovarian cancer (18), gastric cancer (19) and breast cancer (20). For example, SNHG20 was found to be significantly upregulated in HCC and colorectal cancer, and the high expression of SNHG20 was a predictor of poor prognosis (15,17).…”
Section: Introductionmentioning
confidence: 99%